Influence Of Artificial Intelligence On Leadership Communication And Emotional Intelligence In Public Colleges Of Education In Plateau State, Nigeria - Bashir, Aminu Suleiman; INUSA, Busa Abdul’aziz; Mahmud, Ahmed Ibrahim (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigated the adoption of Artificial Intelligence (AI) in leadership communication and the influence of emotional intelligence on AI-driven leadership practices in public Colleges of Education in Plateau State, Nigeria. Guided by the Social Cognitive Theory and Emotional Intelligence Theory, the research employed a descriptive survey design. The target population comprised 1,150 academic and administrative staff across the state’s public Colleges of Education. A sample of 250 respondents was selected using stratified random sampling. Data were gathered through a structured questionnaire and analyzed using descriptive statistics, Pearson correlation, and multiple regression techniques to address three research questions and test three hypotheses. Findings revealed a moderate level of AI adoption for leadership communication, with respondents affirming its contribution to decision-making efficiency and communication clarity. Emotional intelligence was found to significantly moderate the relationship between AI use and leadership performance (R² = 0.453, p < 0.05). Additionally, institutional and infrastructural challenges such as inadequate training and poor internet access were statistically significant barriers to AI integration (R² = 0.465, p < 0.05). Based on these findings, the study recommends the institutionalization of AI training for leadership staff, adoption of emotional intelligence frameworks in administrative procedures, and increased investment in digital infrastructure. This study underscores the importance of combining technological advancement with emotional competence in enhancing leadership effectiveness. Strengthening AI and emotional intelligence capacity can help bridge the leadership communication gap in Nigeria’s tertiary education sector.